Learning Styles and the Use of ICT in University Students within a Competency-Based Training Model (2023)
The purpose of the study was to determine the learning styles (LS) and the use of Information and Communication Technologies (ICT) in university students within a competency-based training model, as well as to identify possible differences related to the frequency of use of ICT in terms of gender. A descriptive and correlational quantitative approach was applied with a non-experimental and transversal design. The study used an intentional non-probabilistic sample of 113 students in undergraduate psychology, public accounting and business administration programs that use a competency-based model at a private Colombian university. The outcome showed no significant differences among LS or in the frequency of ICT use in students with competency-based training. Additionally, the outcome showed a gender gap in which male students had the highest scores for the use of ICT. © 2019, NAER Journal of New Approaches in Educational Research.